Livestock Production In Poland During The Episodes Of Economic Crises: A Retrospective And Current View - Kamila MUSIAŁ (Communications of International Proceedings, 2025)
The aim of this study was to present the selected crises phenomena occurring in Polish agriculture, including livestock production in the 20th. century, and the first two decades of the 21st. century. During the 20th. century the first significant degradation of agriculture was caused by the World War I, which resulted in the lost of 37,5% cattle, 48% horses, 52% pigs and 60% of sheep, compared to pre-war situation. The next and particularly acute agrarian and food crisis in the 1930s, was a direct result of the Great Depression, and again led to profound impoverishment of rural areas. In the begining of 21st. century, in the period of 2006-2007 there were obesreved favorable conditions for agricultural development in Poland, which have been connected with accession to the European Union. However, shortly after, there was another big destabilization of global and, consequently European agricultural markets. That included downturn in demand and prices, particularly for grain, milk, and livestock, and the economy collapsed again. Currently, in the third decade of the 21st. century there is again visible some kind of recession in animal production. This time it results both from changes in the lifestyle and the new EU requirements, which can be difficult to meet, especially by the owners of small farms.
Keywords: animal production; food crises; agriculture in Poland; 20th. and 21st. centuries